(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2024)
The population engaged in agricultural activity is particularly vulnerable to diseases due to a combination of factors associated with their work environment. The present research aims to identify diseases associated with agricultural activity in the San Isidro parish of the province of Manabí, Ecuador. A sample of 92 families was taken, where the data was collected through document review, interviews, surveys and direct observation, and analysis using Microsoft Excel and ArcGIS to obtain descriptive and cartographic results. The San Isidro parish has an area of 277.95 km², where 89.73% of families are mainly engaged in agricultural activities and 7.34% in forestry activities. In this rural area, it was highlighted that there is a prevalence of primary level education with 60.29% of the population, of which 71.56% are economically active. In terms of health, 81.52% have peasant insurance, but only 17.39% are retired; consequently, 98.91% of producers have suffered some illness or parenteral injury due to their daily activities and only 79.35% go to the nearest health center; the most common illness is influenza in the areas closest to the parish capital, followed by spinal problems that affect 42.39% of the population. With this, the research contributes to understanding health in agricultural environments to establish public policies adapted to the needs of the parish, promoting its sustainability and integral development.